Analisis Pelaksanaan Sistem Administrasi Bidang Promosi Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Provinsi Sumatera Selatan - Novaria, Eva; Semil, Nurma; Jimiaty, Jimiaty (@-Publik: Jurnal Administrasi Publik, 2022)
The Office of Investment and One Stop Integrated Services (DPMPTSP) of South Sumatra Province has a vision of "The Main Investment Destination Province Based on Competitive Local Resources to Support Advanced South Sumatra For All". To realize this vision, the Office of Investment and Integrated Services (DMPPTSP) of South Sumatra Province continues to conduct campaigns to attract investors through the investment promotion sector whose task is to plan and encourage the development, implementation and preparation of investment-supporting infrastructure buildings. This research is a descriptive research with a qualitative approach. Data analysis is a qualitative analysis with an interactive model. Based on the results of the study, it can be concluded that the Investment Promotion Office and the Integrated Service Administration System of South Sumatra Province have been implemented according to the applicable procedures and provisions, although not optimal. There are several obstacles in the process, namely: 1) The company/investor has not maximized the supply of LKPM; 2) non-integrated ad serving; 3) Limited investment promotion budget and uncoordinated business cooperation; 4) Lack of reliable sales promotion resources and skills in sales promotion; and 5) lack of coordination with the center, districts/cities and companies.